Field reports form for submitting seasonal observations of Iowa birds, Gerald White, fall 1983 - White, Geraldet al (1983)
An annotated list of birds sighted by Gerald White. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1983. Epson - sheet feed